DEVELOPMENT OF MOBILE LEARNING BASED MEDIA FOR MICROPROCESSOR ENGINEERING SUBJECT IN SMK NEGERI 5 SURABAYA - Raras, Gustav Mandigo Anggana; Munoto, Munoto; Ekohariadi, Ekohariadi (Letters in Information Technology Education (LITE), 2018)
The purpose of this research is to produce a valid teaching media for microprocessor engineering subject named Mikro-X. Mikro-X can be accessed online either using computer or smartphone. The development of Mikro-X is based on ten step R&D by Borg and Gall. In the experiment step two class is used, X-EDK 1 as experiment class and X-EDK 2 as control class. Mikro-X is used in experiment class while conventional media is used in control class. Two class is compared by their learning outcomes (affective, cognitive, and psychomotor). Mikro-X has validity 4.539 (Likert scale) based on four validator responses. On the experiment stage, students who use Mikro-X have a higher learning outcome (affective, cognitive, and psychomotor) than students who use conventional media.